Ice-nucleating particles near two major dust source regions - C. M. Beall; T. C. J. Hill; P. J. DeMott; T. Köneman; M. Pikridas; F. Drewnick; H. Harder; C. Pöhlker; J. Lelieveld; B. Weber; M. Iakovides; R. Prokeš; et al. (Atmospheric Chemistry and Physics, 2022)
Mineral dust and sea spray aerosol represent important sources of ice-nucleating particles (INPs), the minor fraction of aerosol particles able to trigger cloud ice crystal formation and, consequently, influence multiple climate-relevant cloud properties including lifetime, radiative properties and precipitation initiation efficiency. Mineral dust is considered the dominant INP source in many parts of the world due to its ice nucleation efficiency and its sheer abundance, with global emission rates of up to 4700 Tg a −1 . However, INPs emitted from the ocean surface in sea spray aerosol frequently dominate INP populations in remote marine environments, including parts of the Southern Ocean where cloud-resolving model simulations have demonstrated that cloud radiative properties are likely strongly controlled by INPs. Here we report INP concentrations measured in aerosol and seawater samples during Air Quality and Climate Change in the Arabian Basin (AQABA), a shipborne campaign that spanned the Red Sea, Gulf of Aden, Arabian Sea, Arabian Gulf and part of the Mediterranean. In aerosol samples collected within a few hundred kilometers of the first and second ranked sources of dust globally, the Sahara and Arabian Peninsula, INP concentrations ranged from 0.2 to 11 L −1 at − 20 ∘ C with observed ice-active surface site densities ( n s ) 1–3 orders of magnitude below levels predicted by mineral dust INP parameterizations. Over half of the samples (at least 14 of 26) were collected during dust storms with average dust mass concentrations between 150 and 490 µ g m −3 (PM 10 ), as simulated by the Modern-Era Retrospective analysis for Research and Application, version 2 (MERRA-2). The impacts of heat and peroxide treatments indicate that organics dominated the observed ice nucleation (IN) activity at temperatures ≥ − 15 ∘ C with proteinaceous (heat-labile) INPs frequently observed at high freezing temperatures > −10 ∘ C. INP concentrations in seawater samples ranged between 3 and 46 mL −1 at − 19 ∘ C, demonstrating ...